2019
DOI: 10.1038/s41598-019-55389-z
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Evaluation of Hospital Performance of Childbirth Delivery Modes and Associated Factors in the Friuli Venezia Giulia Region (North-Eastern Italy), 2005–2015

Abstract: Cesarean sections (CS) have become increasingly common in both developed and developing countries, raising legitimate concerns regarding their appropriateness. Since improvement of obstetric care at the hospital level needs quantitative evidence, using routinely collected health data we contrasted the performance of the 11 maternity centres (coded with an alphabetic letter A to L) of an Italian region, Friuli Venezia Giulia (FVG), during 2005–15, after removing the effect of several factors associated with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 74 publications
0
24
1
Order By: Relevance
“…The calculation of the PPCS rate may have been slightly inflated, since the respective numerator obtained from CEDAP comprised both planned CS and CS performed after failed induction, distinguished categories which were impossible to disentangle though. However, the crude rate of labour induction was 15.6% out of all births in FVG during 2005-2015 14 , hence the impact of CS for induction failure on the calculation of the PPCS rate was likely marginal in our study.…”
Section: Strengths and Limitationsmentioning
confidence: 66%
See 4 more Smart Citations
“…The calculation of the PPCS rate may have been slightly inflated, since the respective numerator obtained from CEDAP comprised both planned CS and CS performed after failed induction, distinguished categories which were impossible to disentangle though. However, the crude rate of labour induction was 15.6% out of all births in FVG during 2005-2015 14 , hence the impact of CS for induction failure on the calculation of the PPCS rate was likely marginal in our study.…”
Section: Strengths and Limitationsmentioning
confidence: 66%
“…Strengths of this study have been reported elsewhere 13,14,44 . There are, however also some limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
See 3 more Smart Citations